Мохоподібні (Bryophyta) Українських Карпат - Лобачевська, О. (Праці наукового товариства ім. Шевченка, 2003)
Узагальнено результати дослідження бріофлори Українських Карпат: представлена історія бріологічних досліджень реґіону; проаналізовано сучасний склад флори; наведено основні екологічні особливості поширення мохоподібних; проведено географічний аналіз бріофлори та з’ясовано основні етапи її формування на досліджуваній території; подано відомості про рідкісні види Карпат і заходи їх охорони. The results of investigation of bryoflora of the Ukrainian Carpathians are generalized: the
history of bryological research of the region is represented; the present floristic composition of the bryoflora was analyzed; the general ecological peculiarities of Bryophyta distribution are described; the geographical analysis of bryoflora was fulfilled and the basic stages of it’s formation for this territory were defined; the information about the rare species of the Carpathians and the measures of their reservation are given.